2012
DOI: 10.1186/1478-7954-10-14
|View full text |Cite
|
Sign up to set email alerts
|

Mortality trends in Tonga: an assessment based on a synthesis of local data

Abstract: BackgroundAccurate measures of mortality level by age group, gender, and region are critical for health planning and evaluation. These are especially required for a country like Tonga, which has limited resources and works extensively with international donors. Mortality levels in Tonga were examined through an assessment of available published information and data available from the four routine death reporting systems currently in operation.MethodsAvailable published data on infant mortality rate (IMR) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 7 publications
2
31
2
Order By: Relevance
“…Increases in premature adult mortality from non-communicable diseases (NCD) are slowing or halting life expectancy increases in Fiji (Taylor et al 2013), probably in Tonga (Hufanga et al 2012), and possibly in Samoa. Estimates from the 2015 GBD study suggest that life expectancy in Samoan women has made only small gains: from 73 to 74 years between 1990 and 2015; whereas estimates for Samoan men have increased from 66 to 72 years over the same period (Institute for Health Metrics and Evaluation 2016), although incomplete mortality reporting makes all estimates fraught.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in premature adult mortality from non-communicable diseases (NCD) are slowing or halting life expectancy increases in Fiji (Taylor et al 2013), probably in Tonga (Hufanga et al 2012), and possibly in Samoa. Estimates from the 2015 GBD study suggest that life expectancy in Samoan women has made only small gains: from 73 to 74 years between 1990 and 2015; whereas estimates for Samoan men have increased from 66 to 72 years over the same period (Institute for Health Metrics and Evaluation 2016), although incomplete mortality reporting makes all estimates fraught.…”
Section: Discussionmentioning
confidence: 99%
“…The main problem with vital registration is usually under‐enumeration rather than over‐enumeration, and therefore higher rates from vital registration in the past compared to indirect methods are plausible. Vital registration can be subject to over‐enumeration if different sources of registration are added together without de‐duplication, as could happen in Tonga 20,21 or Fiji, 21,22 but in this instance a single source (MoH) was used. Case ascertainment of births and deaths, especially in children, through the Health Department is usually of high standard in small countries where these events are infrequent.…”
Section: Discussionmentioning
confidence: 99%
“…Although Table 50 indicates LE has actually fallen in Tonga, the case study presented in Chapter 5 demonstrated this is not actually the case, and that earlier estimates of LE were likely to be an overestimation (111).…”
Section: Mortality In Transitionmentioning
confidence: 91%
“…Despite studies that suggest estimates derived from local census analyses are the most reliable data on mortality for much of the region (excluding the small islands and territories) (2,93,111,112), country generated reports frequently rely on estimates from international agencies. Table 7 is derived from the most recent MDG progress report published by the Fijian government.…”
mentioning
confidence: 99%